STUDENTS’ PERCEPTIONS ON THE USE OF INSTAGRAM REELS TO STIMULATE STUDENTS’ MOTIVATION IN SPEAKING ENGLISH - Amalia, Adella (Journal of English Language and Literature Teaching, 2022)
Social media may serve as an alternative and innovative medium in teaching and learning during this Covid-19 pandemic. This Study uses Reels Instagram to improve students’ motivation to learning English during the pandemic where learning resources are limited. With using a qualitative research approach especially, a case study. This study aimed to explore how the use of social media, especially Reels Instagram in teaching English for high school students. the data is collected by observing classroom learning, distributing questionnaire and interviewing some selected students. The findings show that social media, especially Reels Instagram serve to improve students’ motivation and interests in learning English. Besides that, some students felt happy and more active because the learning process is different, which made some students motivated to speak English. This study also has another result, where students have pronounce some words or sentences with good fluency. Academically, social media has become a vital tool for some people in daily communication and is also widely used in some schools in the education process, especially Instagram which is one of the most widely used social media platforms among youths and university students. Then, it is serve that social media was the most famous platform in social and education.